A Review of Customer Benefits and Satisfaction with Amanah Products: Evidance Pegadaian Syariah - Sitti Walida Mustamin; Jasri; Widya Nur Indahsari (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2023)
Introduction: Mu'amalah is the activity of interaction between individuals and their surrounding environment. In Islam, this teaching promotes cooperation in everyday life. In the era of globalization, Islamic financial institutions such as Pegadaian Syariah are becoming increasingly vital, offering trust products with strict adherence to Sharia principles. This evaluation becomes a crucial key to measuring product performance and customer satisfaction, supporting the sustainable growth of Islamic financial institutions. Purpose: This research aims to evaluate the benefits provided by Amanah Products at Pegadaian Syariah Central Makassar Branch and measure the level of customer satisfaction with the product. Methodology: The research method used in this study is qualitative descriptive with data analysis techniques including data reduction, data presentation, and drawing conclusions. Findings: The findings of this research reveal that Amanah Products at Pegadaian Syariah offer easy, structured, and inclusive requirements and procedures, facilitating various groups of individuals such as civil servants, employees, and micro-entrepreneurs to obtain vehicle financing without difficulties. The transparent application process also assists customers in meeting their vehicle needs. Customer satisfaction is very high due to the friendly, professional quality of service and structured procedures meeting customer expectations. Customer loyalty is reflected in their intention to continue using Amanah Products. Pegadaian Syariah Central Makassar Branch demonstrates a high level of professionalism, providing equal treatment to all customers, creating an inclusive atmosphere, and facilitating understanding of structured work processes. The quality of service and professionalism build a strong relationship between Pegadaian Syariah and its customers, enhancing long-term trust and loyalty.